Managing Risk Factors through Corporate Governance for Financial Institutions of Pakistan (KASBIT Business Journal, 2013)
Managing risk factors in financial organizations has gained more importance in recentyearsbecause of financial crisis after recession. The purpose of study is to identify the challengesand their proposed solutions to handle the crisis under umbrella of good governance practices.The specific objective of this study is to find out the factors and challenges that effect thebusiness of financial institutions via practicing the good governance. In accordance to thiscritical situation has been evaluated with the help of risk regulatory model that covers theidentifying, measuring evaluating and monitoring techniques for financial institutions inPakistan.This study also emphasis on strategies and ways to eliminate organizational internaland external risk factors through policies and modifying business models in order to get thesustainable business position and organization growth. The research findings based upon thesystematic review of literature and qualitative survey from the industrial experts. This studyreveals that the risk factors directly associated with the sustainable business growth whenorganization pays worthy attention towards the corporate governance. It also empowered theorganization to build a wealthy relationship with the customers and helps to retain the smallinvestment of customer with diversified banking products.
Keywords: Governance practices; Risk management and Control; Financial Institution